Genera of palaearctic Pyrgotidae (diptera, acalyptrata),with nomenclatural notes and a key - Korneyev, V.A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
На основании изучения типовых материалов, описанных И. А. Порчинским, Ф. Генделем, Г. Эндерляйном и Э. Герингом, установлена следующая си¬нонимия: Adapsilia Waga, 1842 = Teliophleps Hering, 1940, syn. n. Adapsilia coarctata Waga, 1842 = Adapsilia alini Hering, 1940, syn. n. Adapsilia mandschurica (Hering, 1940), comb. n. (= Teliophleps mandschurica Hering) = Adapsilia breviantenna Kim et Han, 2001, syn. n. Adapsilia microcera (Portschinsky, 1892) (= Pyrgota microcera Portschinsky, Epicerella microcera: Hendel, 1933, Sooґs, 1984) = Adapsilia tenebrosa Kim et Han, 2001, syn. n. Adapsilia verrucifer Hendel, 1933 = Adapsilia cornugaster Kim et Han, 2001, syn. n. Campylocera Macquart, 1843 = Teliophleps Enderlein, 1942, syn. n. (non Teliophleps Hering) = Dicrostira Enderlein, 1942, syn. n. Campylocera apicalis (Enderlein, 1842), comb. n. (= Teliophleps apicalis Enderlein). Campylocera partitigena (Enderlein, 1942), comb. n. (= Dicrostira partitigena Enderlein). Eupyrgota facialis (Hendel, 1934), comb. n. (= Adapsilia facialis Hendel; ?= E. tigrina Kim et Han, 2000). Eupyrgota griseipennis (Hendel, 1933), comb. n. (= Adapsilia griseipennis Hendel). Eupyrgota wagae (Bigot, 1880), comb. n. (= Adapsilia wagae Bigot). Parageloemyia Hendel, 1934 = Dicranostira Enderlein, 1942, syn. n. Parageloemyia nigrofasciata (Hendel, 1933), comb. n. (= Geloemyia nigrofasciata Hendel) = Parageloemyia ornata Hering, 1940, syn. n. Porpomastix Enderlein, 1942 = Paradapsilia Chen, 1947, syn. n. Porpomastix fasciolata Enderlein, 1942 = Paradap-silia trinotata Chen, 1947, syn. n. Adapsilia hirtoscutellaris Hendel — непригодное название (непра¬вильное первоначальное написание). Род Cardiacera Macquart (= Epicerella Macquart) исключен из числа встречающихся в Палеарктике родов. Представлены переработанная таблица для опре¬деления и обзор родов Pyrgotidae Палеарктической области. Based upon the study of the type specimens described by J. A. Portschinsky, F. Hendel, G. Enderlein and E. Hering, the following synonymy is established. Adapsilia Waga, 1842 = Teliophleps Hering, 1940, syn. n. Adapsilia coarctata Waga, 1842 = Adapsilia alini Hering, 1940, syn. n. Adapsilia mandschurica (Hering, 1940), comb. n. (= Teliophleps mandschurica Hering) = Adapsilia breviantenna Kim et Han, 2001, syn. n. Adapsilia microcera (Portschinsky, 1892) (= Pyrgota microcera Portschinsky, Epicerella microcera: Hendel, 1933, Soo´s, 1984) = Adapsilia tenebrosa Kim et Han, 2001, syn. n. Adapsilia verrucifer Hendel, 1933 = Adapsilia cornugaster Kim et Han, 2001, syn. n. Campylocera Macquart, 1843 = Teliophleps Enderlein, 1942, syn. n. (non Teliophleps Hering) = Dicrostira Enderlein, 1942, syn. n. Campylocera apicalis (Enderlein, 1842), comb. n. (= Teliophleps apicalis Enderlein). Campylocera partitigena (Enderlein, 1942), comb. n. (= Dicrostira partitigena Enderlein). Eupyrgota facialis (Hendel, 1934), comb. n. (= Adapsilia facialis Hendel; ? = E. tigrina Kim et Han, 2000). Eupyrgota griseipennis (Hendel, 1933), comb. n. (= Adapsilia griseipennis Hendel). Eupyrgota wagae (Bigot, 1880), comb. n. (= Adapsilia wagae Bigot). Parageloemyia Hendel, 1934 = Dicranostira Enderlein, 1942, syn. n. Parageloemyia nigrofasciata (Hendel, 1933), comb. n. (= Geloemyia nigrofasciata Hendel) = Parageloemyia ornata Hering, 1940, syn. n. Porpomastix Enderlein, 1942 = Paradapsilia Chen, 1947, syn. n. Porpomastix fasciolata Enderlein, 1942 = Paradapsilia trinotata Chen, 1947, syn. n. Adapsilia hirtoscutellaris Hendel is an unavailable name (incorrect original spelling). The genus Cardiacera Macquart (= Epicerella Macquart) is excluded from the list of genera occurring in Palaearctic Region. An improved key to and a review of genera of the Pyrgotidae known to occur in Palaearctic Region are provided.